Dziecko i dzieciństwo w hagiografii staropolskiej - Sokołowska, Katarzyna (Poznańskie Studia Teologiczne, 2009)
The article is an overview of studies on the theme of childhood and the child as a specific literary hero of old Polish hagiography. Hagiographers tended to render the childhood of the saints within a schematic framework employing an abundant repertoire of rhetoric devices. But hagiography also gives fragmentary descriptions of customs connected with the relations between parents and children as well as with parental care and the bringing up progeny. For hagiographers childhood was above all a foretoken of the saint’s future virtues and works. The child itself, however, was not a suitable paragon to follow so hagiography rarely treated it as a hero in its own right.